2001
DOI: 10.1677/joe.0.1710267
|View full text |Cite
|
Sign up to set email alerts
|

The genetics of signal transduction and the outcome of diagnostic tests in growth retardation

Abstract: The effects of 'normal' genetic variability of signal transduction on endocrine function may be more evident during stimulation tests than is observed in basal states, thereby contributing to a greater understanding of the possible role of signal transduction genetics in the pathogenesis of endocrine disorders. In the present study, we have studied the outcome of growth hormone (GH) stimulation testing by insulin in growth-retarded children in relation to the genotype of ACP1 (acid phosphatase locus 1; also re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…We have reconsidered a previous study (Bottini et al 2001) showing an effect of ACP1 genetic variability on the area under the GH secretory curve during provocative tests.…”
Section: Interaction With Acp1mentioning
confidence: 86%
See 2 more Smart Citations
“…We have reconsidered a previous study (Bottini et al 2001) showing an effect of ACP1 genetic variability on the area under the GH secretory curve during provocative tests.…”
Section: Interaction With Acp1mentioning
confidence: 86%
“…In a previous note, we have shown that the area under the GH secretory curve is greater in subjects with medium-low ACP1 activity than in those with high activity (Bottini et al 2001). ACP1 is a protein tyrosine phosphatase that is able to dephosphorylate the insulin receptor, thus decreasing the effects of insulin (Bottini et al 2002a).…”
Section: Area Under the Gh Secretory Curvementioning
confidence: 95%
See 1 more Smart Citation